2013
DOI: 10.1038/ncb2656
|View full text |Cite|
|
Sign up to set email alerts
|

Intracellular lumen extension requires ERM-1-dependent apical membrane expansion and AQP-8-mediated flux

Abstract: SUMMARYMany unicellular tubes such as capillaries form lumens intracellularly, a process that is not well understood. Here we show that the cortical membrane organizer ERM-1 is required to expand the intracellular apical/lumenal membrane and its actin undercoat during single-cell C.elegans excretory canal morphogenesis. We characterize AQP-8, identified in an ERM-1 overexpression (ERM-1[++]) suppressor screen, as a canalicular aquaporin that interacts with ERM-1 in lumen extension in a mercury-sensitive manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
170
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(180 citation statements)
references
References 72 publications
10
170
0
Order By: Relevance
“…Several mutant strains with aberrant excretory canal morphology have been isolated and used to investigate tubule formation during normal development (e.g., 1-2, 10 -11, 32, 37); these studies have identified cytoskeletal, signaling, and transport proteins as being essential for formation or maintenance of the canals. Recent studies have demonstrated that the excretory canals are extended when worms are shifted between high and low osmolarity (52,56), implying that osmotic pressure and water flux may play important roles in remodeling the excretory Fig. 1.…”
Section: Osmoregulatory Organ Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several mutant strains with aberrant excretory canal morphology have been isolated and used to investigate tubule formation during normal development (e.g., 1-2, 10 -11, 32, 37); these studies have identified cytoskeletal, signaling, and transport proteins as being essential for formation or maintenance of the canals. Recent studies have demonstrated that the excretory canals are extended when worms are shifted between high and low osmolarity (52,56), implying that osmotic pressure and water flux may play important roles in remodeling the excretory Fig. 1.…”
Section: Osmoregulatory Organ Systemsmentioning
confidence: 99%
“…Direct transfer from high to low osmolarity causes swelling and temporary paralysis presumably because of elevated turgor pressure (42,52). After ϳ10 -15 min, swelling subsides and motility is regained by most individuals.…”
Section: Volume Recovery and Wnk/gck VI Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…1A and 1B). Indeed, such hydrostatic pressure was proposed to play important roles in lumen formation and expansion in the gut [12], in Kupffer's vesicle [13] and in brain ventricles [14] in zebrafish, and in the excretory cell [15] and vulva [16] in C. elegans. Moreover, the cylindrical geometry of tubular structures brings along physical constraints that are distinct from those experienced by cells in planar epithelial sheets.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of mutants defective for axon outgrowth has suggested that extension of the basolateral membrane requires the axon outgrowth machinery (Hedgecock et al, 1987). By contrast, extension of the apical membrane appears to depend on osmotic stress and involves the fusion of the peri-apical vesicles with the lumen, which requires a physical interaction between the aquaporin AQP-8 and the apical actin-binding Ezrin-Radixin-Moesin homologue ERM-1 (Gobel et al, 2004;Khan et al, 2013;Kolotuev et al, 2013). Vesicular trafficking is important for canal morphogenesis to control the fusion of canalicular vesicles with the lumen, and/or to recycle proteins and/or lipids that remain to be defined.…”
Section: Promiscuous Microtubule-actin Partnership During Excretory Cmentioning
confidence: 99%